The Role of the Insula in Schizophrenia - Wylie, Korey P. (2010)
Involvement of the insular cortex is a common finding in neuroanatomical studies of schizophrenia, yet its contribution to disease pathology remains unknown. This review describes the normal function of the insula and examines pathology of this region in schizophrenia. The insula is a cortical structure with extensive connections to many areas of the cortex and limbic system. It integrates external sensory input with the limbic system and is integral to the awareness of the body’s state (interoception). Many deficits observed in schizophrenia involve these functions and may relate to insula pathology. Furthermore, reports describing deficits caused by lesions of the insula parallel deficits observed in schizophrenia. Examples of insula-related functions that are altered in schizophrenia include the processing of both visual and auditory emotional information, pain, and neuronal representations of the self. The last of these functions, processing representations of the self, plays a key role in discriminating between self-generated and external information, suggesting that insula dysfunction may contribute to hallucinations, a cardinal feature of schizophrenia.